2014
DOI: 10.1093/jmcb/mju047
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived microvesicles mediate human breast cancer invasion through differentially glycosylated EMMPRIN

Abstract: Tumor cells secrete not only a variety of soluble factors, but also extracellular vesicles that are known to support the establishment of a favorable tumor niche by influencing the surrounding stroma cells. Here we show that tumor-derived microvesicles (T-MV) also directly influence the tumor cells by enhancing their invasion in a both autologous and heterologous manner. Neither the respective vesicle-free supernatant nor MV from benign mammary cells mediate invasion. Uptake of T-MV is essential for the proinv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
130
1
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(145 citation statements)
references
References 35 publications
11
130
1
3
Order By: Relevance
“…In recent years, it has become apparent that metalloproteinases are released directly from the fibroblast plasma membrane in the form of shedding microvesicles . It has also been repeatedly shown that, by doing so, microvesicles affect both matrix invasiveness and cell migration by acting on the integrity of the collagen itself …”
Section: Discussionsupporting
confidence: 53%
“…In recent years, it has become apparent that metalloproteinases are released directly from the fibroblast plasma membrane in the form of shedding microvesicles . It has also been repeatedly shown that, by doing so, microvesicles affect both matrix invasiveness and cell migration by acting on the integrity of the collagen itself …”
Section: Discussionsupporting
confidence: 53%
“…Levels of MVs expressing tumor-associated proteins such as MUC1, EGFR or FAK seem to be elevated in the blood of breast cancer patients 15,16 . Also for Exos, recent studies have shown that blood-derived Exos carrying tumor-specific antigens such as Glypican-1 for pancreatic cancer or Del-1 for breast cancer allow early disease detection with high specificity and sensitivity 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…+ taMP and CD147 + EpCAM -MPs were at day 7 post-OP in median not differing compared to respective pre-OP values ( Figure 4C-4D). We speculate that CD147 + EpCAM − MPs were shed from fibroblast, T-cells, stroma cells, epithelial cells during tumour resection indicating tissue remodelling, migration and cancer cell invasion in which EMMPRIN/CD147 might play role as suggested by others [7,20,21].…”
Section: Discussionmentioning
confidence: 59%
“…+ taMP and CD147 + EpCAM -MPs were at day 7 post-OP in median not differing compared to respective pre-OP values ( Figure 4C-4D). We speculate that CD147 + EpCAM − MPs were shed from fibroblast, T-cells, stroma cells, epithelial cells during tumour resection indicating tissue remodelling, migration and cancer cell invasion in which EMMPRIN/CD147 might play role as suggested by others [7,20,21].Taken together, in vivo cancer cells shed distinct taMP populations with a unique pan-cancer MPs-based signature. Even if each tumour is composed of a mixture of heterogeneous tumour cells, the released EpCAM + and EpCAM + CD147 + taMPs can be reliable detected in the circulation in both primary and metastatic tumour-bearing patients ( Figure 4E).…”
mentioning
confidence: 59%